S-nitrosoglutathione reductases are low-copy number, cysteine-rich proteins in plants that control multiple developmental and defense responses in Arabidopsis - Xu, Shengbao; Guerra, Damian; Lee, Ung; Vierling, Elizabeth (Frontiers in Plant Science, 2013)
S-nitrosoglutathione reductase (GSNOR) is believed to modulate effects of reactive oxygen and nitrogen species through catabolism of S-nitrosoglutathione (GSNO). We combined bioinformatics of plant GSNOR genes, localization of GSNOR in Arabidopsis thaliana, and microarray analysis of a GSNOR null mutant to gain insights into the function and regulation of this critical enzyme in nitric oxide homeostasis. GSNOR-encoding genes are known to have high homology across diverse eukaryotic taxa, but contributions of specific conserved residues have not been assessed. With bioinformatics and structural modeling, we show that plant GSNORs likely localize to the cytosol, contain conserved, solvent-accessible cysteines, and tend to be encoded by a single gene. Arabidopsis thaliana homozygous for GSNOR loss-of-function alleles exhibited defects in stem and trichome branching, and complementation with GFP-tagged GSNOR under control of the native promoter quantitatively rescued these phenotypes. GSNOR-GFP showed fluorescence throughout Arabidopsis seedlings, consistent with ubiquitous expression of the protein, but with especially high fluorescence in the root tip, apical meristem and flowers. At the cellular level we observed cytosolic and nuclear fluorescence, with exclusion from the nucleolus. Microarray analysis identified 99 up- and 170 downregulated genes (≥2-fold; p ≤ 0.01) in a GSNOR null mutant compared to wild type. Six members of the plant specific, ROXY glutaredoxins and three BHLH transcription factors involved in iron homeostasis were strongly upregulated, supporting a role for GSNOR in redox and iron metabolism. One third of downregulated genes are linked to pathogen resistance, providing further basis for the reported pathogen sensitivity of GSNOR null mutants. Together, these findings indicate GSNOR regulates multiple developmental and metabolic programs in plants and offer insight into putative routes of post-translational GSNOR regulation.